Abuso de poder económico, acaparamiento y especulación - Stucchi, Pierino (2021)
This article addresses the recent legislative developments on the crimes of abuse of economic power, hoarding and speculation in the Peruvian jurisdiction, as well as the inconvenience that its validity represents for the proper development of free competition policies. It is concluded that, contrary to what is recommended by international standards, the requirements of regulatory quality have not been met in the context of a pandemic.